Adventures in Minecraft - O'Hanlon, Martin; Whale, David (John Wiley & Sons, 2015)
Efficient markets models assert that the price of each asset is equal to the optimal forecast of its ex-post (or fundamental) value, but the models do not imply that the covariances between prices equal the corresponding covariances of ex-post values. We present bounds for covariances and correlations of prices based on the covariance of ex-post values, and show how such bounds can be tightened using information about forecasting variables. The methods are used to examine the historical covariance between the U.S. and U.K. stock markers 1919-1989. The bounds on the covariance include the actual correlation